Crimes against Women in Varanasi City: A Geographical Analysis - Singh, Ravi S; Rashmi (National Geographical Journal of India, 2022)
Crime against women is partly a result of unequal gender relations that assume men to be superior to women. Women are subjected to rape, abduction, dowry death or their attempts, torture both mental and physical, sexual harassment and trafficking. As per the official data, general reported cognisable crimes have increased in recent years; the rate of increase of those against women is faster. The present study is an attempt to understand the nature of crime against women in Varanasi City in recent past (2009-2013). It is based on crime reporting in the print media. According to the data collected, dowry deaths and abductions were most and least reported crimes in Varanasi city, respectively, during the study period.